Immune checkpoint blockade therapy in head and neck cancer: a review (Update Dental College Journal, 2018)
Head and neck cancer (HNC) is a common malignant tumor, carrying a poor prognosis, and despite advances in oncology, this rate has not improved significantly for decades. It has recently been evaluated that the immunologic checkpoint inhibitors become a novel promising strategic immunotherapy in the treatment of metastatic cancer. Therefore, our current review article will discuss the biological role and impact of the immune checkpoint inhibitor in HNC.Update Dent. Coll. j: 2018; 8 (2): 30-33